(untitled) (Research, Society and Development, 2022)
The current article expresses several approaches that aim to contribute to the development of the human body, through aerobic activities, cycling, running, among others. The study of this research has as its theme The Benefits of the Practice of Physical Exercises in the Recovery of Covid-19, and its general objective is to demonstrate the results from physical exercises in the recovery of Covid-19 and its performance in the immune system. Containing itself as problematic: What benefits does the practice of physical exercises provide in the recovery of Covid-19? In this sense, the methodology applied is a qualitative descriptive literature review research, aiming to help researchers in their scientific studies. In view of this, through the analysis carried out, it was possible to describe the trajectory of the spread of Covid-19, as well as emphasizing such exercises that contribute to recovery and addressing the importance of practicing activity for the construction of the immune system. In conclusion, the importance of demonstrating to other people the importance of practicing physical activities that will favor health.